2008
DOI: 10.1200/jco.2007.14.7116
|View full text |Cite
|
Sign up to set email alerts
|

Wild-Type KRAS Is Required for Panitumumab Efficacy in Patients With Metastatic Colorectal Cancer

Abstract: A B S T R A C T PurposePanitumumab, a fully human antibody against the epidermal growth factor receptor (EGFR), has activity in a subset of patients with metastatic colorectal cancer (mCRC). Although activating mutations in KRAS, a small G-protein downstream of EGFR, correlate with poor response to anti-EGFR antibodies in mCRC, their role as a selection marker has not been established in randomized trials. Patients and MethodsKRAS mutations were detected using polymerase chain reaction on DNA from tumor sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

65
1,989
5
61

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 2,956 publications
(2,120 citation statements)
references
References 36 publications
65
1,989
5
61
Order By: Relevance
“…Cetuximab, a human-mouse chimeric IgG1 monoclonal antibody, was the first EGFR-targeted agent approved for the treatment of colorectal cancer [12,23]. Panitumumab, a fully human IgG2κ monoclonal antibody, was recently approved in the US and Europe as third-line treatment of metastatic colorectal cancer [12,24]. Both antibodies have been shown to reduce the risk of tumor progression and to improve overall survival (OS), progression-free survival (PFS) and quality of life in patients with refractory colorectal cancer [11,23,[25][26][27][28].…”
Section: Egfr and Colorectal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Cetuximab, a human-mouse chimeric IgG1 monoclonal antibody, was the first EGFR-targeted agent approved for the treatment of colorectal cancer [12,23]. Panitumumab, a fully human IgG2κ monoclonal antibody, was recently approved in the US and Europe as third-line treatment of metastatic colorectal cancer [12,24]. Both antibodies have been shown to reduce the risk of tumor progression and to improve overall survival (OS), progression-free survival (PFS) and quality of life in patients with refractory colorectal cancer [11,23,[25][26][27][28].…”
Section: Egfr and Colorectal Cancermentioning
confidence: 99%
“…Considering the molecular basis of EGFR-targeting agents, blocking EGFR at the receptor level will not ablate downstream signaling activities in tumors with KRAS mutations and hence constitutively active RAS proteins. Indeed, several studies have reported that KRAS mutations confer resistance to anti-EGFR monoclonal antibodies [24,48,[61][62][63][64][65]. KRAS mutations are associated with poor responses to therapy, reduced PFS and shorter OS in colorectal cancer patients treated with cetuximab alone or in combination with chemotherapy [48,[62][63][64][65].…”
Section: Kras: a Downstream Target Of Egfr Signalingmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Indeed, KRAS mutations result in constitutively active KRAS proteins that lead to continuous activation of the RAS signaling pathway independently of the upstream stimulation by EGFR ligands. As only patients with wild-type KRAS tumors benefit from therapies with anti-EGFR antibodies, accurate determination of the KRAS mutation status is crucial for ethical and economic reasons.…”
mentioning
confidence: 99%
“…17 Another group reported that panitumumab monotherapy is effective only in patients in whom tumors are wild-type for KRAS, and that consideration of KRAS genotype should be applied in selection of patients with mCRC for this treatment. 5 KRAS mutations are increasingly acknowledged as predictive for resistance to anti-EGFR antibody therapy, and several studies involving first-and subsequent-line treatments suggest that patients with tumors that have KRAS mutations are clinical utility: For KRAS mutation analysis, the EWG found adequate evidence that improved health outcomes are achieved by avoiding ineffective chemotherapy and potential side effects and expediting access to the next most effective treatment. Inadequate evidence was found regarding association of BRAF V600E mutation testing or loss of PTEN expression with improved health outcomes among patients with mCRC undergoing anti-EGFR therapy as compared with patients with tumors bearing wild-type BRAF sequence and PTEN expression levels, respectively.…”
Section: Background and Clinical Context For The Recommendationmentioning
confidence: 99%